2022
DOI: 10.1186/s12955-022-01991-1
|View full text |Cite|
|
Sign up to set email alerts
|

Partners matter: The psychosocial well-being of couples when dealing with endometriosis

Abstract: Background Endometriosis is often associated with severe dysmenorrhea, pelvic pain and dyspareunia and has a high impact on daily life as well as sexuality. Quality of partnership positively influences the course of various diseases and ability to cope with emotional and physical distress. However, studies focusing on the male partners of endometriosis patients are rare, and even less is known about the reciprocal relationship in these couples. Therefore, this study aims to explore the interrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…In addition, we would like to mention that another interesting fact for future studies would be to evaluate the relationship status and partnership of our patients to find out how that might have an impact as well [ 22 ]. Along with Schick et al [ 22 ], the impact of the partner should be taken into account when counseling or treating women with endometriosis. Their study has shown a high interdependence and reciprocal influence from both partners—positively and negatively—concerning psychological distress and sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we would like to mention that another interesting fact for future studies would be to evaluate the relationship status and partnership of our patients to find out how that might have an impact as well [ 22 ]. Along with Schick et al [ 22 ], the impact of the partner should be taken into account when counseling or treating women with endometriosis. Their study has shown a high interdependence and reciprocal influence from both partners—positively and negatively—concerning psychological distress and sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Their study has shown a high interdependence and reciprocal influence from both partners—positively and negatively—concerning psychological distress and sexual satisfaction. The authors state that the impact of endometriosis on the partner has probably been underestimated [ 22 ]. It is conceivable that the impact of a partnership can interfere—positively and negatively—with the well-being and mental situation of endometriosis patients, especially under the circumstances of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that education and awareness of the topic of endometriosis in the relatives and friends of those affected, but also in society, are important factors in supporting affected couples. In addition, (male) partners should be included in the treatment of endometriosis patients, as they can also be affected and restricted by this disease [42].…”
Section: Further Implicationsmentioning
confidence: 99%
“…This is the case, for example, in connection with coping strategies [ 30 ] and self-efficacy [ 28 ]. A study conducted in Heidelberg and Innsbruck indicated that the subjective experience of major stress heightened the negative impact of endometriosis pain not only on the patients, but also on their partners [ 33 ]. Interestingly, social support had a great deal less influence than the (subjectively perceived) absence of understanding for the illness from others.…”
Section: Endometriosis and Partner Relationsmentioning
confidence: 99%